2013
DOI: 10.1002/jbm.a.34753
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdry human amniotic membrane is useful material for tissue engineering: Physical, morphological properties, and safety as the new biological material

Abstract: Human amniotic membrane (AM) has been used widely as graft biomaterial for a variety of clinical applications. But, there are some persistent problems related to the preparation, storage, and sterilization. To resolve these problems, we developed hyperdry AM (HD-AM) using far-infrared rays, depression of air, and microwaves and then sterilized by γ-ray irradiation. To elucidate the benefit of HD-AM as biological materials, compare with the physical and histological properties of HD-AM with a freeze-dried AM (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…This prototype freeze-dried AM was improved by use of trehalose to protect its physical properties during the freezing process (Nakamura et al, 2008b). Most recently, Okabe et al reported that hyper-dry AM, using far-infrared rays, depression of air and microwaves with g-ray irradiation, is a useful biomaterial for tissue engineering (Okabe et al, 2014). In view of the particular T. Nakamura et al / Progress in Retinal and Eye Research xxx (2015) 1e20 13 focus on pathogenic organisms in recent years, suitable sterilization of both native and dried AM is vital, and these developments will contribute to the next generation of AM, using tissue engineering techniques.…”
Section: Dried Ammentioning
confidence: 98%
“…This prototype freeze-dried AM was improved by use of trehalose to protect its physical properties during the freezing process (Nakamura et al, 2008b). Most recently, Okabe et al reported that hyper-dry AM, using far-infrared rays, depression of air and microwaves with g-ray irradiation, is a useful biomaterial for tissue engineering (Okabe et al, 2014). In view of the particular T. Nakamura et al / Progress in Retinal and Eye Research xxx (2015) 1e20 13 focus on pathogenic organisms in recent years, suitable sterilization of both native and dried AM is vital, and these developments will contribute to the next generation of AM, using tissue engineering techniques.…”
Section: Dried Ammentioning
confidence: 98%
“…1 [7,8]. Okabe et al found that the structures of collagen fibers in the connective tissues were not destroyed by the hyperdry device and were more stable than cryopreserved AM [7]. Allen et al also showed that the biochemical composition of the dried AM, including the number of factors such as epidermal growth factor and TGF-β1, were similar to fresh AM [22].…”
Section: Discussionmentioning
confidence: 86%
“…As the temperature inside the hyperdrying device does not exceed 35 • C during drying, it is thought that the beneficial characteristics of fresh amniotic membrane are retained in the dried ␥-irradiated amniotic membrane. 17,[23][24][25] We used xenogenous grafts in this study. We need to repeat experiments with allogeneic grafts, possibly in pigs, and ultimately in carefully-selected patients as previously reported with cryopreserved amniotic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…8 This material has been used clinically in ophthalmology and otology. [15][16][17] We previously reported its use in the oral cavity as a wound dressing after oral procedures, and concluded that it could be used for covering secondary mucosal defects. 18,19 In the present study we have examined its effect on reducing the inhibition of growth and development of the maxilla after repair of cleft palate in rats.…”
Section: Introductionmentioning
confidence: 99%